Statement of some of the advantages attendant upon making St. John' s, Newfoundland a port of call for transatlantic steamers [electronic resource] - Field, Cyrus W. (Cyrus West), 1819-1892. ([London? : s.n.], 1856)
Table. Signed and dated: Cyrus W. Field, London, February 1856. Electronic reproduction. Mode of access: Internet. 44